Marrying the matchmaker - Hedlund, Jody (Hedlund, Jody. Shanahan match, 2026)
"Witty Bellamy McKenna has yet to find a wife and prove to St. Louis's Irish community that he's a capable matchmaker. Zaira Shanahan has ambitious pursuits that contradict her family's wishes and defy societal norms. As a scandal brews, can Bellamy and Zaira's fake match blossom into true love and break their unlucky streak of misfortune?"-- Provided by publisher.